(untitled) (Jurnal Hukum Islam, 2012)
This article emphasizes the importance of Yahya bin Adam’s Kitab al-Kharaj to the investigation of public finance in the second century of Islam (Hijriyah). His work stands out as the accessible terminus a quo documenting the foundations of the ‘traditionistic school’ of economic thinking. Under Abbasid Caliphs, he endeavored to compose policy guidelines of public finance for both believers and officials. He tries to construct a welfare society that aims at not only promoting distributive justice and allocative efficiency but also maintaining combination of right to property, security, autonomy, and liberty. His views on land and taxation policy (kharaj) are enlightening.